Antocianinas presentes nos frutos do jambolão (Syzygium cumini L.): estudo da extração e aplicação em sistemas de liberação controlada - Sabino, Luiz Bruno de Sousa (2019)
Anthocyanins are plant pigments belonging to the flavonoids class, recognized by the colours that they express in nature and by their different biological properties. Due to their highlighted technological potential, several researches have focused on identifying possible sources for extraction and application of anthocyanins. In this context the aim of this research was to determine the best conditions for the extraction of the anthocyanins present in jambolan fruit (Syzygium cumini L.), to apply the extract in the tablets based on carboxymethyl starch and evaluate the anthocyanins release in simulated medium. The response surface methodology (RSM), was used to optimize the experimental conditions for anthocyanin extraction using pressurized liquid extraction (PLE), bath ultrasound extraction (BUE) and probe ultrasound extraction (PUE). A central face centered design was used to optimize the extraction parameters (ethanol concentration, cycles number, time, temperature and ultrasound potency) in terms of anthocyanin concentration (mg.g-1). The highest recovery of anthocyanins was obtained from the process performed with PUE and the optimal conditions were: ultrasound power 300 W, extraction time 7.5 min and ethanol concentration equal to 79.6%. Under these conditions the concentration of anthocyanins was 60.5 mg.g-1, that was close to the value predicted by the model. The anthocyanins delphinidin-3,5-diglucoside, petunidine-3,5-diglucoside, malvidine-3,5-diglucoside were tentatively identified by UPLC-ESI-QTOF-MS in all extracts, which demonstrated that the methods did not promoted qualitative changes in jambolan anthocyanin profile. In this research, carboxymethyl starch (CMS) was synthesized and used as excipient to evaluate the release of anthocyanins into gastric (SGF) and intestinal fluids (SIF). The structural analyses demonstrated a strong interaction between the components of the tablets and the formation of a complex between the anthocyanins and the CMS. The dissolution profiles varied according to the medium and to the tablet formulation. In general, the release of anthocyanins was higher in neutral medium (SIF), being controlled by swelling and erosion of the polymer matrix. After 9 hours of assay, simulating the gastrointestinal tract, the C4 (formed by the anthocyanin-CMS complex) tablet presented more than 90% of the anthocyanins in dissolution, showing the higher percentage released when compared to the other tablets. Under the same dissolution conditions, C4 presented a strong correlation with the Korsmeyer-Peppas model (R2 = 0.98) and, according to the value of n (0.41), the release of anthocyanins from this tablet was controlled by the diffusion effect. The optimization of the C4 formulation allowed the complete release of the pigments either rapidly (30 min) or prolonged (12 hours), demonstrating that anthocyanins can be released in different regions of the gastrointestinal tract. The release of 70% of the anthocyanins resulted in the reduction of 50% of the ABTS●+ radical activity present in the medium and the antioxidant activity of these substances was higher in the intestinal environment (327μM Trolox.g-1) compared to the gastric (271 μM Trolox.g-1). The interaction with the CMA provided greater stability to the anthocyanin extract, resulting in the formation of a potential carrier system for the gastrointestinal delivery, bringing more information to the study of these pigments as active agents in several formulations intended for supplements and therapies.